Gender inequalities in excess adiposity and anaemia combine in a large double burden of malnutrition gap detrimental to women in an urban area in North Africa. Issue 8 (6th April 2016) - Traissac, Pierre; El Ati, Jalila; Gartner, Agnès; Ben Gharbia, Houda; Delpeuch, Francis
Abstract: Objective: The nutrition transition has exacerbated the gender gap in health in the Middle East and North Africa region as the increase in excess adiposity has been much higher among women than men. This is not exclusive of the persistence of anaemia, generally also more prevalent among women. We assessed the magnitude and sociodemographic factors associated with gender inequality vis-à-vis the double burden of excess adiposity and anaemia. Design: Cross-sectional study, stratified two-stage cluster sample. BMI (=weight/height 2 ) ≥25·0 kg/m 2 defined overweight and BMI≥30·0 kg/m 2 obesity. Anaemia was defined as Hb <120 g/l for women, <130 g/l for men. Gender inequalities vis-à-vis the within-subject coexistence of excess adiposity and anaemia were assessed by women v . men relative prevalence ratios (RPR). Their variation with sociodemographic characteristics used models including gender × covariate interactions. Setting: Greater Tunis area in 2009–2010. Subjects: Adults aged 20–49 years (women, n 1689; men, n 930). Results: Gender inequalities in excess adiposity were high (e.g. overweight: women 64·9 % v . men 48·4 %; RPR=2·1; 95 % CI 1·6, 2·7) and much higher for anaemia (women 38·0 % v . men 7·2 %; RPR=8·2; 95 % CI 5·5, 12·4). They were striking for overweight and anaemia (women 24·1 % v . men 3·4 %; RPR=16·2; 95 % CI 10·3, 25·4). Gender inequalities in overweight adjusted for covariates increased with age but decreased with professional activity and household wealth score; gender inequality in anaemia or overweight and anaemia was more uniformly distributed. Conclusions: Women were much more at risk than men, from both over- and undernutrition perspectives. Both the underlying gender-related and sex-linked biological determinants of this remarkable double burden of malnutrition inequality must be addressed to promote gender equity in health.